Innovative development of human capital as an important factor of the economic growth of construction industry - Shovkivska, V. (Ways to Improve Construction Efficiency, 2019)
In Ukraine, with relatively large amounts of investment in human capital, investment efficiency remains relatively low, so the problem of increasing innovative human capital by improving the efficiency of investing and improving the efficiency of public institutions responsible for its formation and development, which is the basis of economic growth and competitiveness construction industry. The purpose of the article is to conduct analytical studies of the process of investing in the innovative development of human capital and foreign experience of investing in the development of human capital. It is determined that investments in innovative development of human capital depend to a large extent on the expenditures of the consolidated budget of Ukraine for socio-cultural events and education, which have significantly decreased in recent years (for education - from 19.1% in 2014 to 16.8% in 2018). ., for health care - from 10.9% in 2014 to 9.3% in 2018, for social protection - by 1.7%). Insufficient government funding for education, health care, spiritual and physical development has hindered the development of innovative human capital, economic growth and increased competitiveness of the construction industry in recent years. The article discusses the impact of innovative human capital development on the economic growth of the construction industry. Much attention is paid to investing in the innovative development of human capital of Ukraine and the progressive foreign experience of solving this problem. It is noted that the orientation of the Ukrainian economy and construction industry in particular on the formation and development of innovative human capital should be ensured by comprehensive measures implemented by central and territorial bodies of state power, bodies of management of the construction industry, employers and representatives of education and science, public employment service by deepening engagement with the EU through existing partnership programs with European countries on innovative human capital development.